DIGESTIBILIDADE DA MATÉRIA SECA E PROTEÍNA BRUTA DO RESÍDUO SECO DE PADARIA EM OVINOS. - VIEIRA, P. F.; CALDARA, F. R.; ANDRADE, G. A.; REZENDE, A. V.; GIOSO, M. M.; LEIRA, M. H.; VILELA, H. H. (Ars Veterinaria, 2009)
A avalia